Genome-Wide Identification, Characterization, and Expression Profiling of the Legume BZR Transcription Factor Gene Family - Li, Yueying; He, Liangliang; Li, Jing; Chen, Jianghua; Liu, Changning (Frontiers in Plant Science, 2018)
The BRASSINAZOLE-RESISTANT (BZR) family of transcription factors (TFs) are positive regulators in the biosynthesis of brassinosteroids. The latter is a class of steroid hormones that affect a variety of developmental and physiological processes in plants. BZR TFs play essential roles in the regulation of plant growth and development, including multiple stress-resistance functions. However, the evolutionary history and individual expression patterns of the legume BZR genes has not been determined. In this study, we performed a genome-wide investigation of the BZR gene family in seven legume species. In total, 52 BZR genes were identified and characterized. By analyzing their phylogeny, we divided these BZR genes into five groups by comparison with orthologs/paralogs in Arabidopsis thaliana. The intron/exon structural patterns and conserved protein motifs of each gene were analyzed and showed high group-specificities. Legume BZR genes were unevenly distributed among their corresponding genomes. Genome and gene sequence comparisons revealed that gene expansion of the BZR TF family in legumes mainly resulted from segmental duplications and that this family has undergone purifying selection. Synteny analysis showed that BZR genes tended to localize within syntenic blocks conserved across legume genomes. The expression patterns of BZR genes among various legume vegetative tissues and in response to different abiotic stresses were analyzed using a combination of public transcriptome data and quantitative PCR. The patterns indicated that many BZR genes regulate legume organ development and differentiation, and significantly respond to drought and salt stresses. This study may provide valuable information for understanding the evolution of BZR gene structure and expression, and lays a foundation for future functional analysis of the legume BZR genes by species and by gene.